Role of vitamin D supplementation in the prevention of URTI (upper respiratory tract infections) among highly physically active individuals - Marzec, Jakub; Łukasz, Krzysztof; Musioł, Aleksandra; Gwałt, Paweł; Nowakowski, Michał; Rakuś, Magdalena (Journal of Education, Health and Sport, 2026)
Introduction: High-intensity physical exercise, characteristic of professional sports and military training, is associated with a significantly increased risk of upper respiratory tract infections (URTI). Such a phenomenon, described as the “J-curve”, is explained by the post-exercise “open window” effect, which is effectively state of transient immunosuppression. At the same time, vitamin D deficiency is particularly common among professional athletes, especially during winter at higher latitudes. Methods: The aim of this narrative review was to assess the effectiveness of vitamin D interventions in the prevention of URTI based on randomized controlled trials and recent meta-analyses Results: Despite a lack of evidence in general population meta-analyses for the effectiveness of vitamin D in preventing infections, some athlete-focused trials have confirmed measurable benefits in targeted high-risk groups. It is shown that a daily supply of vitamin D in athletes and recruits training in winter effectively corrects deficiencies, significantly shortens the duration and severity of URTI symptoms. Conclusions: These observations suggest that maintaining adequate vitamin D status in athletes exposed to intense physical stress, particularly during winter months, may contribute to improved mucosal immune defence and reduced severity of URTI symptoms. Potential mechanisms may involve vitamin D receptor–mediated induction of an antimicrobial peptides such as LL-37 and modulation of local inflammatory responses.